23.2k views
2 votes
Find p(12) - p(-3) given p(x) = x + 6

User Aurast
by
4.0k points

1 Answer

4 votes

Answer:

The correct answer to this problem is 15.

Explanation:

To solve this problem, we first need to evaluate p(12) and p(-3). To do this, we simply plug in the number in parentheses into each occurrence of x in the equation given. This is modeled below.

p(12)= 12+6 = 18

p(-3)= -3+6=3

Now, we must use these values we have found in our other expression.

p(12)-p(-3)

18-3

15

Therefore, your answer is 15.

Hope this helps!

User Natsu
by
4.9k points